Ca Fluxes in Single Twitch Muscle Fibers - Curtis, B. A. (The Rockefeller University Press, 1966)
Ca influx and efflux in single twitch muscle fibers were determined by the movement of (45)Ca. The isotope was assayed by counting the center 1 cm of a fiber while it was in nonradioactive Rnger's solution. The average resting influx in 1.0 mM Ca Ringer's was 0.26 pM Ca/cm(2). sec for 5 to 20 min influx periods. The average additional influx upon stimulation in 1.0 mM Ca was 0.73 pM Ca/cm(2). twitch. The efflux after both resting and stimulated (45)Ca influx can be described by a single exponential curve with an average time constant of 125 min. This relationship is an indication of Ca exchange with a single intracellular compartment. This compartment contains an estimated 47% of the total muscle Ca at 1.0 mM Ca. When the Ca in the Ringer was reduced to 0.5 mM Ca, both the resting and stimulated Ca fluxes decreased. When Ca was raised to 1.8 mM, the stimulated influxes increased but the resting influx did not.